Essence of Information Support of Public Authority Activities Under the Conditions of Informational Society Development . - Naboka, Lyudmila; Nikitenko, Oleksiy (Pressing Problems of Public Administration, 2019)
In the current conditions, information has a very signi cant impact on the functioning of various social systems, both at the national and international levels. In this regard, the information provision of management processes is becoming one of the most important types of support in virtually all spheres of society. Information provision of public authorities is the process of creating the optimal conditions for meeting information needs and the implementation of of cial duties in public authorities on the basis of the formation and use of information resources. It is based on the widespread use of new information technologies, means of computer and communication technologies, it allows to increase ef ciency of work of public and commercial organizations by several times, optimize according to the speci ed criteria of resource use, reduce the circulation of documents with the transition to electronic management technologies. That is why the de nition of information provision of public authorities should be interpreted as a functional complex that provides the organic interaction of technical means, methods and technologies of work with information, the possibility of purposeful continuous collection, search, grouping, analysis, storage and dissemination of information, as well as the receipt of timely, reliable and complete information about the status and parameters of the operation of certain management objects at speci ed intervals or according to their requests; which displays information about the status of the managed object and forms the basis for making managerial decisions, generates information that consists of important data and does not allow to distract for unnecessary and cumbersome information, contributing to the effective implementation of the management process and taking into account the information needs of all users.